(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2023)
This article discusses the staging of Álbum de família by Grupo Galpão from Belo Horizonte in 1990. Created in 1982 and recognized as one of the most important groups in the country, Galpão has a long trajectory, and many stagings that dialogue with social issues through popular lens. The editing of Nelson Rodrigues dramatic text, directed by Eid Ribeiro was a milestone in the group´s career, especially because it was a tragic play. In this text, we discuss the assembly project and also the importance of Nelson Rodrigues work and the meaning of its reinterpretation in BH at the beginning of the 1990s.